Circulating adhesion molecules after short-term exposure to particulate matter among welders. Issue 1 (6th September 2009) - Fang, S C; Eisen, E A; Cavallari, J M; Mittleman, M A; Christiani, D C
Abstract : Background: Studies from several countries indicate that welders experience increased risk of mortality and morbidity from ischaemic heart disease. Although the underlying mechanisms are unclear, vascular responses to particulate matter contained in welding fumes may play a role. To investigate this, we studied the acute effects of welding fume exposure on the endothelial component of vascular function, as measured by circulating adhesion molecules involved in leukocyte adhesion (sICAM-1 and sVCAM-1) and coagulation (vWF). Methods: A panel of 26 male welders was studied repeatedly across a 6 h work-shift on a high exposure welding day and/or a low exposure non-welding day. Personal PM2.5 exposure was measured throughout the work-shift. Blood samples were collected in the morning (baseline) prior to the exposure period, immediately after the exposure period, and the following morning. To account for the repeated measurements, we used linear mixed models to evaluate the effects of welding (binary) and PM2.5 (continuous) exposure on each blood marker, adjusting for baseline blood marker concentration, smoking, age and time of day. Results: Welding and PM2.5 exposure were significantly associated with a decrease in sVCAM-1 in the afternoon and the following morning and an increase in vWF in the afternoon. Conclusions: The data suggest that welding and short-term occupational exposure to PM2.5 may acutely affect the endothelial component of vascular function.